ADMINISTRATIVE MEASURES FOR PROTECTION OF LIVING ENVIRONMENT IN THE REPUBLIC MACEDONIA - Risteski, Temelko; Dzhafche, Sejdefa; Karovska, Biljana; Jovanoska, Ilina; Popova, Tanja; Mihtaroski, Emrah (European Scientific Journal, ESJ, 2014)
Administrative measures for protection of the living environment in the Republic of Macedonia are: normative and regulatory measures, organizational measures, control and supervision measures and sanction measures. Normative regulatory measures include the adoption of laws and sublaws regulations for the normative regulation of social relations in the field of environmental protection. Organizational measures are reduced to organizing the system of state bodies and social institutions for the protection of the environment and determining their competences. Control measures are monitoring all activities of social control and inspection conducted by state bodies and social institutions for the smooth and efficient implementation in life the provisions on the protection of the living environment contained in the Law on Nature Protection and in the Law on the Living Environment of the Republic of Macedonia. Sanction measures include measures of detection and prosecution of offenders for acts of misconduct against the environment undertaken by administrative and other state bodies of the Republic of Macedonia.